Coated aluminum foil and its preparation method and application

By using the combination of materials such as polyvinylidene fluoride and nano-silica in the coated aluminum foil, the problems of limited improvement in hydrophilic properties and weak decontamination ability of existing coated aluminum foils are solved, and higher hydrophilicity, pollution resistance and adhesion are achieved, and service life is extended.

CN118994984BActive Publication Date: 2025-05-02T&L CHEM (YINGKOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411224066.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-05-02
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The hydrophilic performance of existing coated aluminum foils is limited, the stain removal and self-cleaning capacity are weak, and the coating adhesion is poor.

Method used

The structure is adopted that includes an aluminum foil substrate, a transition layer and a functional coating. The transition layer contains polyvinylidene fluoride and nanosilica and water-absorbing silicone particles. Through the combination and treatment of these materials, the hydrophilicity, stain resistance and adhesion of the coating are improved.

Benefits of technology

It significantly improves the self-cleaning ability and stain resistance of the coating, enhances the hydrophilicity and adhesion of the coating, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application discloses a coated aluminum foil and a preparation method and application thereof, which relates to the technical field of coating materials, and specifically comprises: an aluminum foil substrate, a transition layer and a functional coating; the transition layer comprises polyvinylidene fluoride; the transition layer is arranged on the aluminum foil substrate by phase separation; the functional coating is arranged on at least one surface of the aluminum foil substrate; the functional coating comprises a hydrophilic layer; the single-side coating amount of the functional coating is 1g / m 2 ‑1.5g / m 2 ; Improves the self-cleaning ability and anti-fouling performance of the coating, further improves the hydrophilicity of the coating, enhances the adhesion of the coating, and extends the service life of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coating materials, and in particular to a coated aluminum foil and a preparation method and application thereof. Background Art

[0002] Coated aluminum foil is a product that is specially treated on the surface of aluminum foil and coated with one or more layers of materials. The aluminum foil coating of the air conditioner heat exchanger adopts organic coating, which is convenient for construction and presents good functionality. When the air conditioner is just turned on, when no condensed water is formed on the surface of the heat exchanger, the oil smoke is adsorbed on the internal surface of the air conditioner, causing the heat exchanger to be polluted and the hydrophilicity to be reduced. After the polar molecules on the surface of the air conditioner heat exchanger coating are adsorbed by foreign pollutants, the hydrophilicity is reduced, and the pollutants on the surface of the heat exchanger are difficult to be washed off. The oil stains gather and breed bacteria to produce odor. At present, the coating structure of ordinary air conditioner heat exchangers includes an anti-corrosion layer and a hydrophilic layer, of which the hydrophilic layer accounts for about 25% of the coating amount of the organic coating. In general environments, the corrosive media in the environment where the air-conditioning indoor unit is located are not strong, mainly oil fume pollution and a small amount of polluting gases such as SO2. There is no obvious corrosion of the aluminum foil. Instead, a large amount of oil accumulates on the surface, and there is a strong odor. As the use time increases, the polar groups in the hydrophilic coating are gradually consumed, and the hydrophilicity is seriously attenuated. When the hydrophilic angle reaches 70°, the air-conditioning performance is significantly reduced, which may cause problems such as water blowing.

[0003] For example, the Chinese patent application number CN202010870261.4 discloses a coated aluminum foil and its preparation method and application. The coated aluminum foil provided by the invention includes: an aluminum foil substrate and a functional coating, wherein the functional coating is arranged on at least one surface of the aluminum foil substrate; the functional coating includes at least a hydrophilic layer; the single-sided coating amount forming the hydrophilic layer accounts for ≥35% of the single-sided coating amount forming the functional coating. The coated aluminum foil provided by the invention can avoid the degradation of the performance of the hydrophilic coating due to the consumption of time, thereby improving the hydrophilic effect of the coated aluminum foil and the long-term effectiveness of the hydrophilic performance, and improving the decontamination ability.

[0004] The above-mentioned solution has limited improvement in the hydrophilicity of the coated aluminum foil, weak decontamination and self-cleaning capabilities, and poor adhesion of the coating. Summary of the invention

[0005] The embodiments of the present application solve the problems in the prior art that the hydrophilic performance of the coated aluminum foil is limited, the decontamination ability and self-cleaning ability are weak, and the coating adhesion is poor by providing a coated aluminum foil and a preparation method and application thereof; the self-cleaning ability and anti-fouling performance of the coating are improved, the hydrophilic performance of the coating is further improved, the coating adhesion is enhanced, and the service life of the coating is extended.

[0006] The present application embodiment provides a coated aluminum foil, specifically comprising:

[0007] Aluminum foil substrate, transition layer and functional coating;

[0008] The transition layer includes polyvinylidene fluoride;

[0009] The transition layer is disposed on the aluminum foil substrate by phase separation;

[0010] The functional coating is disposed on at least one surface of the aluminum foil substrate;

[0011] The functional coating comprises a hydrophilic layer;

[0012] The single-sided coating amount of the functional coating is 1g / m2-1.5g / m2;

[0013] The coating of the hydrophilic layer comprises, by weight: 1-10 parts of hydroxy acrylic monomer, 8-30 parts of carboxyl acrylic monomer, 10-40 parts of other acrylic monomers, 2-5 parts of nano-silicon dioxide, 0.5-3 parts of initiator, 0.5-2 parts of auxiliary agent, and 30-200 parts of water;

[0014] The other acrylic monomers are amide acrylic monomers and epoxy acrylic monomers;

[0015] Further, the specific steps are as follows:

[0016] S1, mixing nano-silica, hydroxyl acrylic monomer, carboxyl acrylic monomer, additives and water at 50°C-70°C, ultrasonically dispersing, and then mixing with other acrylic monomers at 50°C-90°C, adding an initiator, reacting at 80°C-90°C for 30min-50min, and then adjusting the solid content to 30%-60% with water to obtain a hydrophilic layer coating containing nano-silica particles;

[0017] S2. Coating a hydrophilic layer coating on at least one surface of the aluminum foil substrate to form a functional coating to obtain a coated aluminum foil containing a hydrophilic layer of nano-silicon dioxide particles.

[0018] Furthermore, the particle size of the nano-silicon dioxide is 10-50 nm; the thickness of the hydrophilic layer is ≥5 μm.

[0019] Furthermore, the preparation of the transition layer comprises the following specific steps:

[0020] S11, cleaning, degreasing, and drying the aluminum foil substrate to obtain a pretreated aluminum foil substrate;

[0021] S12, dissolving polyvinylidene fluoride in a dimethylacetamide solution to obtain a polymer solution, adding water, and mixing well to obtain a transition layer solution;

[0022] S13, the transition layer solution is evenly coated on the surface of the aluminum foil substrate, and placed in an environment with a temperature of 40-50° C. and a relative humidity of 30-50% for 6-10 hours to form a porous transition layer.

[0023] Furthermore, in step S12, the mass percentage of the polymer solution concentration is 10%-30%, the mass ratio of water to the polymer solution is 1:(5-8); and the thickness of the transition layer is ≥3 μm.

[0024] Furthermore, the transition layer solution also contains water-absorbing silica gel particles.

[0025] Furthermore, the mass of the water-absorbing silica gel particles is 5%-20% of the transition layer solution.

[0026] Furthermore, the particle size of the water-absorbing silica gel particles is 0.5-2 μm.

[0027] Furthermore, the water-absorbing silica gel particles also contain bubbles.

[0028] The above-mentioned coated aluminum foil is applied to heat exchangers which are in a chemically corrosive and oily environment for a long time.

[0029] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:

[0030] First, nano-silica particles have good chemical and thermal stability, which can enhance the weather resistance and chemical corrosion resistance of the coating and extend the service life of the coating; a strong interaction force is formed between the nano-particles and the coating matrix, which improves the adhesion of the coating and prevents the coating from falling off; regular self-cleaning reduces the accumulation of oil stains on the surface of the heat exchanger, avoids the negative impact of oil stains on the heat exchange efficiency, and maintains the long-term and efficient operation of the equipment;

[0031] Secondly, the porous transition layer increases the surface roughness of the aluminum foil, provides more surface area and attachment points, enhances the adhesion of subsequent coatings, and improves the stability and durability of the coatings; the microporous structure of the transition layer can store water, providing a source of water for the subsequent hydrophilic layer, and can maintain the hydrophilicity and self-cleaning ability of the coating; during use, the water stored in the transition layer can be gradually released to help clean the coating surface and extend the self-cleaning cycle;

[0032] Third, the water-absorbing silica gel particles have good water absorption performance and can absorb and store a large amount of water. When heated, the water-absorbing silica gel particles can release the stored water, maintain the wet state of the hydrophilic layer, and enhance the self-cleaning effect; the water-absorbing silica gel particles in the transition layer work together with the hydrophilic layer to make it easy for water molecules to spread on the surface of the coating to form a water film, thereby taking away the oil and impurities attached to the surface of the coating, and further improving the self-cleaning ability of the coating; the water-absorbing silica gel particles can reduce the accumulation of oil on the surface of the coating, reduce the pollution of the hydrophilic layer, and avoid the influence of oil on the heat exchange efficiency, thereby extending the service life of the coated aluminum foil in a high oil pollution environment; the transition layer containing water-absorbing silica gel particles can improve the adhesion and stability of the coating, prevent the coating from falling off, and improve the overall durability of the coating;

[0033] Fourthly, by concentrating the bubble-containing water-absorbing silica gel particles on the surface of the hydrophilic layer, the contact area between the particles and water can be increased to the maximum, thereby improving the water absorption speed and efficiency; the hydrophilic layer itself can improve the hydrophilicity of the coated aluminum foil, and the direct contact of the bubble-containing water-absorbing silica gel particles can further enhance the hydrophilicity, making the surface easier to absorb and retain water; the bubble-containing water-absorbing silica gel particles are enriched on the surface of the transition layer and contact the hydrophilic layer as much as possible, which can guide the uniform distribution of water and reduce the uneven accumulation of water on the coating surface, thereby avoiding local over-wetting or drying; the internal bubbles can enhance the water-absorbing particles The structural strength can prevent it from bursting due to water absorption and expansion during use, thereby extending the service life of the coating. At the same time, the presence of bubbles can increase the elasticity of the coating, buffer the external impact, and protect the hydrophilic layer from damage. After the surface of the hydrophilic layer is enriched with bubble-containing water-absorbing silica gel particles, the water can be more evenly covered on the surface of the coating, which can wash away the dust and stains on the surface and further improve the self-cleaning ability. During the use of the heat exchanger, the evenly distributed water can more effectively participate in the heat exchange process, improve the heat exchange efficiency, reduce energy consumption, and enhance the overall user experience of using products containing this coating. DETAILED DESCRIPTION

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0035] Embodiment 1: Coated aluminum foil, specifically comprising:

[0036] Aluminum foil substrate and functional coating;

[0037] The functional coating is disposed on at least one surface of the aluminum foil substrate;

[0038] The functional coating comprises a hydrophilic layer;

[0039] The coating weight of the functional coating on one side is 1g / m 2 -1.5g / m 2 ;

[0040] The coating of the hydrophilic layer comprises, by weight: 1-10 parts of hydroxy acrylic monomer, 8-30 parts of carboxyl acrylic monomer, 10-40 parts of other acrylic monomers, 2-5 parts of nano-silicon dioxide, 0.5-3 parts of initiator, 0.5-2 parts of auxiliary agent, and 30-200 parts of water;

[0041] The other acrylic monomers are amide acrylic monomers and epoxy acrylic monomers;

[0042] The preparation method of the coated aluminum foil comprises the following specific steps:

[0043] S1, mixing nano-silica, hydroxyl acrylic monomer, carboxyl acrylic monomer, additives and water at 50°C-70°C, ultrasonically dispersing, and then mixing with other acrylic monomers at 50°C-90°C, adding an initiator, reacting at 80°C-90°C for 30min-50min, and then adjusting the solid content to 30%-60% with water to obtain a hydrophilic layer coating containing nano-silica particles;

[0044] Wherein, the particle size of nano-silicon dioxide is 10-50nm;

[0045] S2, coating a hydrophilic layer coating on at least one surface of the aluminum foil substrate to form a functional coating, thereby obtaining a coated aluminum foil containing a hydrophilic layer of nano-silicon dioxide particles;

[0046] Wherein, the thickness of the hydrophilic layer is ≥5 μm;

[0047] The following experiments were conducted on the coated aluminum foil and its preparation method of this embodiment: (i) The first hydrophilic layer: the coating weight is 1.0 g / m 2 The coating composition of the first hydrophilic layer includes, by weight: 1 part of hydroxy acrylic acid monomer, 8 parts of carboxyl acrylic acid monomer, 5 parts of amide acrylic acid monomer, 5 parts of epoxy acrylic acid monomer, 2 parts of nano-silicon dioxide, 0.5 parts of sodium persulfate, 0.5 parts of sodium dodecylbenzene sulfonate, and 40 parts of water;

[0048] Aluminum foil substrate;

[0049] Second hydrophilic layer: coating weight is 1.0g / m 2 The coating composition of the second hydrophilic layer includes, by weight: 1 part of hydroxy acrylic acid monomer, 8 parts of carboxyl acrylic acid monomer, 5 parts of amide acrylic acid monomer, 5 parts of epoxy acrylic acid monomer, 2 parts of nano-silicon dioxide, 0.5 parts of sodium persulfate, 0.5 parts of sodium dodecylbenzene sulfonate, and 40 parts of water;

[0050] The total coating weight on one side of the coated aluminum foil in this example is 1.0 g / m 2 ;

[0051] The preparation method of the coated aluminum foil is as follows: a polyurethane rubber roller is used to apply a hydrophilic coating on the upper and lower surfaces of an aluminum foil substrate, the linear speed ratio of the coating roller and the belt roller is controlled at 0.9-1.3, and the coating is cured at 240° C.-245° C. for 10-15 seconds to obtain the coated aluminum foil;

[0052] The preparation method of the hydrophilic layer coating is as follows: according to the composition of the hydrophilic layer coating, nano-silica, hydroxyl acrylic acid monomer, carboxyl acrylic acid monomer, sodium dodecylbenzene sulfonate and water are mixed at 60°C, and then amide acrylic acid monomer and epoxy acrylic acid monomer are added, and stirred in a mixer at 65°C-75°C for 20 minutes, and then sodium persulfate is added, and the mixture is reacted at 80°C-90°C for 40 minutes, and then the solid content is adjusted with water;

[0053] (II) The first hydrophilic layer: coating weight is 1.5g / m 2 The coating composition of the first hydrophilic layer includes, by weight: 10 parts of hydroxy acrylic acid monomer, 30 parts of carboxyl acrylic acid monomer, 20 parts of amide acrylic acid monomer, 20 parts of epoxy acrylic acid monomer, 5 parts of nano-silicon dioxide, 3 parts of sodium persulfate, 2 parts of sodium dodecylbenzene sulfonate, and 170 parts of water;

[0054] Aluminum foil substrate;

[0055] Second hydrophilic layer: coating weight is 1.5g / m 2 The coating composition of the second hydrophilic layer includes, by weight: 10 parts of hydroxy acrylic acid monomer, 30 parts of carboxyl acrylic acid monomer, 20 parts of amide acrylic acid monomer, 20 parts of epoxy acrylic acid monomer, 5 parts of nano-silicon dioxide, 3 parts of sodium persulfate, 2 parts of sodium dodecylbenzene sulfonate, and 170 parts of water;

[0056] The total coating weight on one side of the coated aluminum foil in this example is 1.5 g / m 2 ;

[0057] (III) The first hydrophilic layer: coating weight is 1.3g / m 2 The coating composition of the first hydrophilic layer includes, by weight: 8 parts of hydroxy acrylic acid monomer, 28 parts of carboxyl acrylic acid monomer, 9 parts of amide acrylic acid monomer, 8 parts of epoxy acrylic acid monomer, 3.5 parts of nano-silicon dioxide, 2 parts of sodium persulfate, 1 part of sodium dodecylbenzene sulfonate, and 48 parts of water;

[0058] Aluminum foil substrate;

[0059] Second hydrophilic layer: coating weight is 1.3g / m 2The coating composition of the second hydrophilic layer includes, by weight: 8 parts of hydroxy acrylic acid monomer, 28 parts of carboxyl acrylic acid monomer, 9 parts of amide acrylic acid monomer, 8 parts of epoxy acrylic acid monomer, 3.5 parts of nano-silicon dioxide, 2 parts of sodium persulfate, 1 part of sodium dodecylbenzene sulfonate, and 48 parts of water;

[0060] The total coating weight on one side of the coated aluminum foil in this example is 1.3 g / m 2 ;

[0061] The comparative example adopts the method of Chinese patent application number CN202010870261.4 to prepare the coated aluminum foil, which is different from the present embodiment (III) in that the hydrophilic layer does not contain nano-silicon dioxide;

[0062] The coated aluminum foils of (i) to (iii) and the comparative example are made into heat exchanger fins, and then the prepared heat exchanger fins are assembled into a heat exchanger with a size of 25 cm×35 cm; the test method is as follows: the blended oil is heated to 300°C to generate oil vapor, the heat exchanger sample is suspended above, and the refrigeration is turned on for 3 hours + stopped for 2 hours as one cycle. After different cycles, the hydrophilic angle of the fins, the heat transfer amount, and the weight of residual oil on the heat exchanger are tested;

[0063] 1. Test the change of hydrophilic angle on the fin: refer to the method specified in GB / T 22638.9, add distilled water to the droplet regulator, fix it on the main unit, rotate the micrometer head, make an appropriate amount of distilled water (10μL) form a droplet on the needle, move the droplet to the surface of the sample, and make the droplet in the center of the eyepiece. After the droplet is left on the sample for 60 seconds, when the droplet no longer spreads, rotate the crosshairs in the eyepiece to make the tangent line at the contact point between the droplet and the coating. The angle between the tangent line and the fixed crosshairs is the contact angle, and this contact angle is the hydrophilic angle;

[0064] 2. Heat exchange performance test: low temperature and wet working conditions (7 / 6 dry-wet bulb, -2 coolant inlet), 1.5m / s (constant static pressure -13Pa), test heat exchange capacity;

[0065] 3. Adhesion test: Refer to GB / T 9286 and use the cross-cut method to test adhesion;

[0066] The test results are shown in the following table:

[0067] Table 1

[0068]

[0069] Table 2

[0070]

[0071] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0072] It can be seen from Table 1 and Table 2 that, as the test period is prolonged, the coated aluminum foil containing nano-silicon dioxide has a smaller hydrophilic angle, a larger heat exchange capacity, a smaller amount of residual oil, and a stronger adhesion than the comparative example, and the increase in the amount of coating can further improve the coating performance; compared with the present embodiment, the comparative example has limited improvement in the hydrophilic performance of the coated aluminum foil, weak decontamination ability and self-cleaning ability, and poor coating adhesion. The addition of nano-silicon dioxide in the present embodiment enhances the hydrophilicity and self-cleaning performance of the coating, improves the adhesion of the coating, and the increase in the amount of coating can further improve the hydrophilicity and self-cleaning performance of the coating;

[0073] Nano-silica particles form a micro-nano rough structure on the coating surface, which enhances the wettability of the coating surface, making it easier for water molecules to spread and form a film on the coating surface, and can remove oil and impurities attached to the coating surface, thereby improving the self-cleaning ability of the coating. Nano-silica particles themselves have a certain degree of hydrophilicity and can form hydrogen bonds with water molecules, further enhancing the hydrophilicity of the coating.

[0074] The presence of nano-silica particles increases the roughness of the coating surface. The high specific surface area and surface activity of nano-particles make it more difficult for oil molecules to accumulate on the coating surface, making it difficult for low surface energy substances such as oil to stably adhere to the coating surface and easily washed away by water, thus reducing the accumulation of oil.

[0075] Nano-silica particles have good chemical and thermal stability, which can enhance the weather resistance and chemical corrosion resistance of the coating and extend the service life of the coating; a strong interaction force is formed between the nano-particles and the coating matrix, which improves the adhesion of the coating and prevents the coating from falling off; regular self-cleaning reduces the accumulation of oil stains on the surface of the heat exchanger, avoids the negative impact of oil stains on the heat exchange efficiency, and maintains the long-term and efficient operation of the equipment.

[0076] Embodiment 2: The above embodiment 1 improves the self-cleaning ability and anti-fouling performance of the coating, enhances the adhesion of the coating, and extends the service life of the coating by adding nano-silicon dioxide particles to the hydrophilic layer. In order to improve the hydrophilicity and adhesion of the coating, further improvements are made on the basis of embodiment 1.

[0077] Before coating the coating to form the functional coating in step S2, a transition layer is also coated on the aluminum foil substrate. The specific steps for preparing the transition layer are as follows:

[0078] S11, cleaning, degreasing, and drying the aluminum foil substrate to obtain a pretreated aluminum foil substrate;

[0079] S12, dissolving polyvinylidene fluoride in a dimethylacetamide solution to obtain a polymer solution, adding water, and mixing well to obtain a transition layer solution;

[0080] The mass percentage of the polymer solution concentration is 10%-30%, and the mass ratio of water to the polymer solution is 1:(5-8);

[0081] S13, evenly coating the transition layer solution on the surface of the aluminum foil substrate, placing it in an environment with a temperature of 40-50° C. and a relative humidity of 30-50% for 6-10 hours, so that the transition layer solution is completely cured to form a porous transition layer;

[0082] Wherein, the thickness of the transition layer is ≥3 μm;

[0083] The following experiment was conducted on the coated aluminum foil and its preparation method of this embodiment. The first hydrophilic layer had a coating weight of 1.3 g / m 2 The coating composition of the first hydrophilic layer includes, by weight: 8 parts of hydroxy acrylic acid monomer, 28 parts of carboxyl acrylic acid monomer, 9 parts of amide acrylic acid monomer, 8 parts of epoxy acrylic acid monomer, 3.5 parts of nano-silicon dioxide, 2 parts of sodium persulfate, 1 part of sodium dodecylbenzene sulfonate, and 48 parts of water;

[0084] Transition layer: coating weight is 0.3g / m 2 ; The mass percentage of the polymer solution concentration is 15%, and the mass ratio of water to polymer solution is 1:6;

[0085] Aluminum foil substrate;

[0086] Transition layer: coating weight is 0.3g / m 2 ; The mass percentage of the polymer solution concentration is 15%, and the mass ratio of water to polymer solution is 1:6;

[0087] Second hydrophilic layer: coating weight is 1.3g / m 2 The coating composition of the second hydrophilic layer includes, by weight: 8 parts of hydroxy acrylic acid monomer, 28 parts of carboxyl acrylic acid monomer, 9 parts of amide acrylic acid monomer, 8 parts of epoxy acrylic acid monomer, 3.5 parts of nano-silicon dioxide, 2 parts of sodium persulfate, 1 part of sodium dodecylbenzene sulfonate, and 48 parts of water;

[0088] The total coating weight on one side of the coated aluminum foil in this example is 1.3 g / m 2 ;

[0089] The preparation method of the coated aluminum foil is as follows: a transition layer solution is applied to the upper and lower surfaces of an aluminum foil substrate using a polyurethane rubber roller, and the linear speed ratio of the coating roller and the belt roller is controlled at 0.9-1.3. After coating, the aluminum foil substrate is placed in an environment of 40-50° C. and 30-50% relative humidity for 8 hours. After the transition layer solution is cured, an aluminum foil substrate containing a porous transition layer is obtained.

[0090] The hydrophilic layer coating is applied by a polyurethane rubber roller, the linear speed ratio of the coating roller and the belt roller is controlled at 0.9-1.3, and the coating is cured at 240° C.-245° C. for 10-15 seconds to obtain a coated aluminum foil;

[0091] Among them, the preparation method of the transition layer is as follows: according to the composition of the transition layer coating, polyvinylidene fluoride is dissolved in a dimethylacetamide solution, and stirring is performed while adding until the polyvinylidene fluoride is completely dissolved to form a uniform polymer solution, and an appropriate amount of water is added to the polymer solution at a mass ratio of 1:6 between water and polymer solution, and stirring is continued until the mixture is uniform to obtain a transition layer solution.

[0092] Compared with the comparative example, the difference between this embodiment and the comparative example is that the coated aluminum foil in this embodiment contains a transition layer and the hydrophilic coating in this embodiment contains nano-silicon dioxide; compared with embodiment 1 (iii), the difference between this embodiment and the coated aluminum foil in this embodiment is that the coated aluminum foil in this embodiment contains a transition layer;

[0093] The test results of this embodiment, the comparative example and embodiment 1 (iii) are as follows:

[0094] Table 3

[0095]

[0096] Table 4

[0097]

[0098] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0099] It can be seen from Tables 3 and 4 that the introduction of the transition layer further improves the hydrophilicity of the coating. As the test period increases, the change in the hydrophilic angle becomes slower. The addition of the transition layer improves the long-term stability of the coating. The porous transition layer enhances the bonding force between the coating and the aluminum foil substrate, thereby improving the overall heat transfer efficiency. The microporous structure of the transition layer can store water, which is gradually released during use, reducing its accumulation on the coating surface.

[0100] The porous transition layer increases the surface roughness of the aluminum foil, provides more surface area and attachment points, enhances the adhesion of subsequent coatings, and improves the stability and durability of the coatings;

[0101] The microporous structure of the transition layer can store water, providing a water source for the subsequent hydrophilic layer, and maintaining the hydrophilicity and self-cleaning ability of the coating. During use, the water stored in the transition layer can be gradually released to help clean the coating surface and extend the self-cleaning cycle.

[0102] By adjusting the porosity and pore size of the transition layer, the self-cleaning and corrosion resistance properties of the aluminum foil can be further optimized. At the same time, the compatibility and overall performance between different coatings can be improved. The transition layer serves as a buffer layer between the aluminum foil substrate and subsequent coatings, which can protect the aluminum foil substrate from direct environmental erosion, thereby extending the service life of the aluminum foil.

[0103] Embodiment 3: The above-mentioned embodiment 2 directly forms a porous transition layer on the surface of the aluminum foil substrate. The porous transition layer can store moisture and improve the adhesion of the coating. In order to enable the coated aluminum foil to maintain the cleanliness and high efficiency of the hydrophilic layer during long-term use, further improvements are made on the basis of embodiment 2.

[0104] The transition layer solution also contains water-absorbing silica gel particles;

[0105] By stirring and mixing, the water-absorbing silica gel particles are uniformly dispersed in the transition layer solution to form a transition layer containing the water-absorbing silica gel particles;

[0106] The mass of the water-absorbing silica gel particles is 5%-20% of the transition layer solution; the particle size of the water-absorbing silica gel is 0.5-2μm.

[0107] The difference between this embodiment and the second embodiment is that the transition layer solution in this embodiment contains water-absorbing silica gel particles whose mass is 10% of the transition layer solution;

[0108] The test results of this embodiment and embodiment 2 are as follows:

[0109] Table 5

[0110]

[0111] Table 6

[0112]

[0113] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0114] It can be seen from Tables 5 and 6 that the addition of water-absorbing silica gel particles can further improve the hydrophilicity of the coating. At the same time, since the water-absorbing silica gel particles can store and release water, they can maintain the wet state and self-cleaning ability of the coating. Therefore, the heat transfer capacity of the heat exchanger is improved and the amount of residual oil on the heat exchanger is reduced.

[0115] The water-absorbing silica gel particles have good water absorption performance and can absorb and store a large amount of water. When heated, the water-absorbing silica gel particles can release the stored water to maintain the wet state of the hydrophilic layer and enhance the self-cleaning effect. The water-absorbing silica gel particles in the transition layer work together with the hydrophilic layer to make it easy for water molecules to spread on the coating surface to form a water film, thereby taking away the oil and impurities attached to the coating surface, further improving the self-cleaning ability of the coating.

[0116] Water-absorbing silica gel particles can reduce the accumulation of oil on the coating surface, reduce the pollution of the hydrophilic layer, and avoid the influence of oil on the heat exchange efficiency, thereby extending the service life of the coated aluminum foil in a high oil pollution environment; the transition layer containing water-absorbing silica gel particles can improve the adhesion and stability of the coating, prevent the coating from falling off, and improve the overall durability of the coating;

[0117] By adjusting the content and distribution of water-absorbing silica gel particles, the water absorption rate and water release rate of the coating can be adjusted, so that the coating can adapt to different usage environments and improve the adaptability and flexibility of the coating.

[0118] Embodiment 4: Embodiment 3 mentioned above achieves long-term self-cleaning of oil stains on the surface of the hydrophilic layer by adding water-absorbing silica gel particles into the transition layer and spraying a hydrophilic layer on the surface of the transition layer. In order to improve the hydrophilicity of the hydrophilic layer, further improvements are made on the basis of Embodiment 3.

[0119] The steps for preparing water-absorbing silica gel particles containing bubbles inside are as follows:

[0120] Put the silica gel raw material into the high temperature melting equipment and heat it to a molten state;

[0121] The foaming agent is uniformly mixed into the silica gel through a mixing device so that the foaming agent is fully dispersed;

[0122] Continue to heat the mixed silica gel to the decomposition temperature of the foaming agent, so that the foaming agent quickly decomposes and produces gas;

[0123] After the foaming agent is decomposed, the silica gel is poured into the cooling equipment for cooling;

[0124] The cooled silica gel particles are ground and sieved to obtain the required bubble-containing water-absorbing silica gel particles.

[0125] The difference between this embodiment and the third embodiment is that the water-absorbing silica gel particles in this embodiment contain bubbles;

[0126] The test results of this embodiment and embodiment 3 are as follows:

[0127] Table 7

[0128]

[0129] Table 8

[0130]

[0131] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0132] As shown in Tables 7 and 8, the addition of water-absorbing silica gel particles containing bubbles into the transition layer further improves the hydrophilicity, heat transfer efficiency and oil resistance of the coating while maintaining good adhesion;

[0133] By making the water-absorbing silica gel particles contain bubbles, when the transition layer is phase-separated, the silica gel particles are closer to the outer surface of the transition layer away from the aluminum foil substrate, and after the water-absorbing layer is coated, the water-absorbing silica gel particles containing bubbles are enriched on the surface of the hydrophilic layer; by enriching the water-absorbing silica gel particles containing bubbles on the surface of the hydrophilic layer, the contact area between the particles and water can be increased to the maximum, thereby improving the water absorption speed and efficiency; the hydrophilic layer itself can improve the hydrophilicity of the coated aluminum foil, and the direct contact of the water-absorbing silica gel particles containing bubbles can further enhance the hydrophilicity, making the surface easier to absorb and retain water;

[0134] The bubble-containing water-absorbing silica gel particles are enriched on the surface of the transition layer and contact the hydrophilic layer as much as possible, which can guide the uniform distribution of water and reduce the uneven accumulation of water on the coating surface, thereby avoiding local over-wetting or drying; the internal air bubbles can enhance the structural strength of the water-absorbing particles, prevent them from bursting due to water absorption and expansion during use, and extend the service life of the coating. At the same time, the presence of bubbles can increase the elasticity of the coating, buffer external impacts, and protect the hydrophilic layer from damage; after the bubble-containing water-absorbing silica gel particles are enriched on the surface of the hydrophilic layer, water can cover the coating surface more evenly, wash away dust and stains on the surface, and further improve the self-cleaning ability; during the use of the heat exchanger, the evenly distributed water can more effectively participate in the heat exchange process, improve the heat exchange efficiency, reduce energy consumption, and enhance the overall user experience of using products containing this coating.

[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Coated aluminum foil, characterized in that: Specifically include: Aluminum foil substrate, transition layer and functional coating; The transition layer includes polyvinylidene fluoride; The transition layer is disposed on the aluminum foil substrate by phase separation; The functional coating is disposed on at least one surface of the aluminum foil substrate; The functional coating comprises a hydrophilic layer; The coating weight of the functional coating on one side is 1g / m 2 -1.5g / m 2 ; The coating of the hydrophilic layer comprises, by weight: 1-10 parts of hydroxy acrylic monomer, 8-30 parts of carboxyl acrylic monomer, 10-40 parts of other acrylic monomers, 2-5 parts of nano-silicon dioxide, 0.5-3 parts of initiator, 0.5-2 parts of auxiliary agent, and 30-200 parts of water; The other acrylic monomers are amide acrylic monomers and epoxy acrylic monomers; The preparation method of the coated aluminum foil comprises the following specific steps: S1, mixing nano-silica, hydroxyl acrylic monomer, carboxyl acrylic monomer, additives and water at 50°C-70°C, ultrasonically dispersing, and then mixing with other acrylic monomers at 50°C-90°C, adding an initiator, reacting at 80°C-90°C for 30min-50min, and then adjusting the solid content to 30%-60% with water to obtain a hydrophilic layer coating containing nano-silica particles; S2, coating a hydrophilic layer coating on at least one surface of the aluminum foil substrate to form a functional coating, thereby obtaining a coated aluminum foil containing a hydrophilic layer of nano-silicon dioxide particles; The preparation of the transition layer comprises the following specific steps: S11, cleaning, degreasing, and drying the aluminum foil substrate to obtain a pretreated aluminum foil substrate; S12, dissolving polyvinylidene fluoride in a dimethylacetamide solution to obtain a polymer solution, adding water, and mixing well to obtain a transition layer solution; S13, uniformly coating the transition layer solution on the surface of the aluminum foil substrate, placing it in an environment with a temperature of 40-50° C. and a relative humidity of 30-50% for 6-10 hours to form a porous transition layer; The transition layer solution also contains water-absorbing silica gel particles; The water-absorbing silica gel particles also contain bubbles.

2. The coated aluminum foil according to claim 1, characterized in that The particle size of the nano silicon dioxide is 10-50nm; the thickness of the hydrophilic layer is ≥5μm.

3. The coated aluminum foil according to claim 1, characterized in that In step S12, the mass percentage of the polymer solution concentration is 10%-30%, and the mass ratio of water to the polymer solution is 1:(5-8); the thickness of the transition layer is ≥3 μm.

4. The coated aluminum foil according to claim 1, characterized in that The mass of the water-absorbing silica gel particles is 5%-20% of the transition layer solution.

5. The coated aluminum foil according to claim 1, characterized in that The particle size of the water-absorbing silica gel particles is 0.5-2 μm.

6. A use of the coated aluminum foil according to any one of claims 1 to 5, characterized in that: Applicable to heat exchangers in chemical corrosion and oil pollution environments for a long time.

Citation Information

Patent Citations

  • Coating aluminum foil as well as preparation method and application thereof

    CN114106604A

  • Heat exchanger, air conditioner outdoor unit and air conditioner

    CN209763331U